(untitled) (Philological Studies, 2021)
The anthology Slovenia’s Best for Young Readers (2020) comprises of 44 contemporary Slovenian creators of literary works aimed at children and young adults and serves as a starting point for discussion. The methodology establishes a selection of authors and their texts in the anthology (at least three works of children’s or young adult literature, awards and nominations in the last ten years) and a comparative analysis of rewarded literary genres and the chosen creators’ poetics. The exception are authors who have received awards for their life’s work and in general no longer receive current awards but are crucial for the development of the contemporary Slovenian children’s and/or young adult literature (Svetlana Makarovič, Neža Maurer, Miroslav Košuta, Slavko Pregl, Boris A. Novak) and have been active since the 1970s. The comparison of literary works which have received awards in the last decade and the authors’ complete works showcases several quality creators who stand out in the last decade: Peter Svetina and Anja Štefan have received important several awards, followed by Nataša Konc Lorenzutti, Vinko Möderndorfer, Lila Prap, Andrej Rozman, Bina Štampe Žmavc, and Janja Vidmar, who have received awards or nominations. Special attention is also paid to creators of original picture books (Prap, K. Musil, Peklar, Wang) and literary genres. The analysis of the latter shows the most productive patterns of contemporary Slovenian children’s and young adult literature, namely fairy tales, short contemporary stories, and contemporary young adult novels. There is a noticeable divide between the most-awarded and most-read works; the authors who receive the highest number of awards are not always most-read.